2014
DOI: 10.1002/asi.23024
|View full text |Cite
|
Sign up to set email alerts
|

Beyond bag‐of‐words: Bigram‐enhanced context‐dependent term weights

Abstract: While term independence is a widely held assumption in most of the established information retrieval approaches, it is clearly not true and various works in the past have investigated a relaxation of the assumption. One approach is to use n-grams in document representation instead of unigrams. However, the majority of early works on n-grams obtained only modest performance improvement. On the other hand, the use of information based on supporting terms or "contexts" of queries has been found to be promising. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 39 publications
2
18
0
2
Order By: Relevance
“…Subsequently, Dang, Luk, and Allan () extended the work to include n ‐grams in the B&D procedure. In particular, they showed that including bigrams ( n = 2) could improve retrieval performance over unigram B&D, while larger values of n did not lead to further improvement.…”
Section: Model Formulationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, Dang, Luk, and Allan () extended the work to include n ‐grams in the B&D procedure. In particular, they showed that including bigrams ( n = 2) could improve retrieval performance over unigram B&D, while larger values of n did not lead to further improvement.…”
Section: Model Formulationsmentioning
confidence: 99%
“…In Dang et al. (), a bigram is defined as an ordered pair of words in a document after stop‐word removal. An additional requirement is that the adjacent members ( t i , t i+1 ) should not be separated by any punctuation, excluding hyphens, in the document.…”
Section: Model Formulationsmentioning
confidence: 99%
See 3 more Smart Citations